2021
DOI: 10.1002/oby.23074
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Self‐Reported Weight History and Sarcopenic Obesity in Adults with Knee Osteoarthritis

Abstract: The purpose of this study was to examine associations between self-reported weight history and sarcopenic obesity in adults with advanced knee osteoarthritis (OA). Methods: Self-reported weight history was collected from n = 151 adults (58.9% female) with knee OA and BMI ≥30 kg/m 2 in a cross-sectional study. Body composition was assessed using dual-energy x-ray absorptiometry. Sarcopenic obesity was defined as appendicular skeletal muscle mass, adjusted by BMI, <0.51 kg/m 2 in females and <0.79 kg/m 2 in male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Firstly, SP increases the risk of OA. In recent years, studies have demonstrated a correlation of varying intensity between SP and OA ( Jin et al, 2017 ; Vlietstra et al, 2019 ; Dalle and Koppo, 2020 ; Godziuk et al, 2021 ). Decreased muscle strength is the main feature of SP and previous experiments have demonstrated that decreased muscle strength or muscle weakness is a risk factor for the development and progression of OA ( Tanaka et al, 2019 ; Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, SP increases the risk of OA. In recent years, studies have demonstrated a correlation of varying intensity between SP and OA ( Jin et al, 2017 ; Vlietstra et al, 2019 ; Dalle and Koppo, 2020 ; Godziuk et al, 2021 ). Decreased muscle strength is the main feature of SP and previous experiments have demonstrated that decreased muscle strength or muscle weakness is a risk factor for the development and progression of OA ( Tanaka et al, 2019 ; Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%